Pemanfaatan Sampah Organik Menjadi Eco Enzyme Bersama Masyarakat Dusun Kwayuhan Kabupaten Magelang - Avina Wafiroh; Revo Hardiawan; Iwan Hardi Saputro; Suryanto Suryanto (Universitas Negeri Semarang, 2026)
The abundant organic waste in households and the agricultural sector is often not utilized properly, leading to ineffective waste management and negative environmental impacts. The utilization of organic waste into eco enzyme by the KKN GIAT 9 UNNES team in Munggangsari Village aims to address the issue of organic waste management that has not been optimally utilized, especially among farmers and housewives. This program is conducted through socialization and training on producing eco enzyme, an environmentally friendly product made from the fermentation of organic kitchen waste. This activity involves the mothers in Kwayuhan Hamlet and is carried out in three stages: preparation, implementation, and monitoring and evaluation. The results of this program indicate an increase in participants' awareness and skills in processing organic waste into useful products, such as natural fertilizers for agriculture. Thus, this program not only helps reduce waste accumulation but also encourages innovation and creativity in waste management.